Comparative analysis of the larvicidal activity of temephos (EC50) and novaluaron (EC10) to control Anopheles stephensi in Sri Lanka. (February 2023) - Jude, Justin; Gunathilaka, Nayana; Udayanga, Lahiru; Fernando, Deepika; Premarathne, Prasad; Wickremasinghe, Rajitha; Abeyewickreme, Wimaladharma
Abstract: Background: Anopheles stephensi was first recorded in the coastal area of Mannar District, Sri Lanka, in December 2016. Since then, this vector has been isolated from other districts in the Northern and Eastern Provinces of Sri Lanka. Chemical control is the main arm of vector control that can be used to reduce the vector densities within a short period. Thus, the present study aimed at evaluating the efficacy of using selected insecticides for the control of An. stephensi larvae. Method: The third and fourth instar larval stages of An. stephensi (F2 generation) of field mosquitoes that were caught using cattle baited net trap collections from Columbuthurai, Kurunagar, and Navanthurai areas in Jaffna District, Sri Lanka, were obtained from the laboratory colony established at Jaffna. Batches of 100 larvae were taken for experiments and introduced separately to a concentration series of temephos and novaluron (0.04–400 ppm). A control test was also performed at each setup without introducing insecticides. The mortality rates of An. stephensi larvae exposed to different concentrations of larvicides were recorded at 1, 24 and 48-h intervals. The experiment was replicated five times at individual concentrations for each selected chemical. Data were analyzed using the General Linear Model (GLM) and Probit analysis. Results: The highest mortality rate (100%) at a 1-h exposure period was observed from temephos at >100 ppm. The mortality rates varied significantly for different concentrations and larvicides ( p < 0.05). At 24-h of the exposure period, the 100% mortality of An. stephensi larvae were observed from both temephos and novaluron even at 0.04 ppm. Conclusion: Both temephos and novaluron reported 100% mortality rates in An. stephensi larvae at 1-h and 24-h exposure periods. Based on the findings, temephos and novaluron can be recommended as effective larvicides for chemical-based control of An. stephensi in Jaffna, Sri Lanka. Further, it is recommended to conduct a field-based study, where habitat types and water quality are highly heterogeneous and may affect the residual activity. Highlights: The highest mortality rate (100%) at a 1-h exposure period was observed from temephos at >100 ppm. Temephos indicated the highest mortality rate in Anopheles stephensi larvae at 1-h exposure period. All exposed larvae after 24-h died in both temephos and novaluron at 0.05 ppm concentration.